Rough country - Sanford, John (London : Pocket, 2010)
aWhile competing in a fishing tournament in a remote area of northern Minnesota, Minnesota Bureau of Criminal Apprehension investigator Virgil Flowers gets a call from Lucas Davenport to investigate a murder at a nearby resort, where a woman has been shot while kayaking. The more he digs, the more he discovers the arrows of suspicion that point in many directions--then he finds that this is not the first murder, that there was a second, seemingly unrelated one, the year before
Keywords: Police -- Minnesota -- Fiction; Murder -- Investigation -- Fiction; Suspense -- Fiction; Mystery -- Fiction